THE DEGREE TO WHICH ENGLISH STUDENT LANGUAGE TEACHERS PRACTICE THE COMMUNICATIVE APPROACH IN TEACHING THE DEVELOPED CURRICULUM "ENGLISH FOR IRAQ" FROM THE POINT OF VIEW OF ACADEMIC SUPERVISORS - Niaam Ali Hasan (Scholars Digest Publishing, 2025)
English language teaching in Iraq has witnessed clear development in recent years, especially in light of the trend towards adopting modern teaching approaches, including the communicative approach, which aims to activate the use of language in real life situations, away from memorization and indoctrination, with the introduction of this approach into the primary school curricula, specifically in English for Iraq books, it has become important to ensure that teachers –especially student teachers in the practical training phase – can practice it effectively. The researcher followed the descriptive analytical approach, and the sample was selected using a simple random approach consisting of (50) male and female students from the fourth stage in the English Language Department in the application stage, the researcher prepared a note card to measure the teaching practices of the communicative approach for English language teacher students, and the psychometric properties of the two tools were verified, the results showed that the degree of teaching practices of the communicative approach was average, in addition to the presence of a statistically significant increase in practices attributed to the gender variable.
Keywords: English Language, Student Teachers, Communicative Approach, Developed Curriculum